Assessment of the relationship between religion, spirituality and well-being among young people of Kazakhstan - M. Ақмади; Г. Кенжакимова; Р. Умбет (Хабаршы. Психология және социология сериясы)
The study investigates and evaluates the relationship between religion, spirituality, and well-being among young people. The study aims to understand how Kazakh youth's religiosity and spirituality affect their well-being. The importance of the study lies in its significant contribution to understanding social changes in Kazakhstan, providing both empirical evidence and conceptual ideas on the relationship between the aspects mentioned above. The research methods are based on the measurement of the Duke University Religiosity Index (DUREL) for assessment of organizational, non-organizational, and internal religiosity, and the Pemberton Happiness Index and the Gallup Healthways Well-being Index were also used to measure the well-being of respondents. The study included 2,654 participants from all regions of Kazakhstan, using quotas based on region, age group, and gender, ensuring data representativeness. The results of the study showed that religious and spiritual people feel more comfortable, with a high level of positive emotions and a lower level of negative ones such as stress and depression. Whereas atheists and agnostics, despite higher rates of optimism about future perceptions, face greater difficulties in managing stress. The value of the study is that it provides new evidence on how religious and spiritual factors affect youth well-being. The work contributes to understanding how religious beliefs contribute to emotional well-being. The practical significance of the study is that its results can be used as supporting material in the development of programs aimed at young people, taking into account religious and spiritual factors. The data obtained complement existing literature on the influence of religion and spirituality on well-being, opening up new possibilities for further research in this field.